Effects of manipulating expression of acetyl-CoA carboxylase I in Brassica napus L. embryos. (December 2000) - Sellwood, C.; Slabas, A. R.; Rawsthorne, S.
Abstract : Acetyl-CoA carboxylase I (ACCase I) in developing oilseed rape embryos is predominantly cystosolic, based upon measurement of its propionyl-CoA carboxylase activity. Reduction of ACCase I by antisense expression reduces seed lipid content and affects carbohydrate metabolism.